Do Our Patients Have Enough to Eat? Food Insecurity among Urban Low-income Cancer Patients - Gany, Francesca (J Health Care Poor Underserved, 2014)
This study assessed the prevalence and predictors of food insecurity among a cohort of underserved oncology patients at New York City cancer clinics. A demographic survey and the U.S. Household Food Security Survey Module were administered. A multivariate General Linear Model Analysis of Covariance was used to evaluate predictors of food insecurity. 404 completed the surveys. 18% had very low, 38% low, 17% marginal, and 27% high food security. The Analysis of Covariance was statistically significant (F(7, 370) = 19.08; p < 0.0001; R-Square = 0.26). Younger age, Spanish language, poor health care access, and having less money for food since beginning cancer treatment were significantly associated with greater food insecurity. This cohort of underserved cancer patients had rates of food insecurity nearly 5 times that of the state average. More research is needed to better understand the causes and impact of food insecurity among cancer and chronic disease patients.